Ferulic Acid as an Anti-Inflammatory Agent: Insights into Molecular Mechanisms, Pharmacokinetics and Applications - Jiaying Liu; Yu Guan; Le Yang; Heng Fang; Hui Sun; Ye Sun; Guangli Yan; Ling Kong; Xijun Wang (Pharmaceuticals, 2025)
Ferulic acid (FA), a hydroxycinnamic acid derivative, is a key bioactive component in traditional medicinal plants including Angelica sinensis and Asafoetida. Accumulating evidence supports its therapeutic efficacy in inflammatory disorders, such as rheumatoid arthritis (RA) and ulcerative colitis (UC). FA exerts anti-inflammatory effects through (1) the regulation of inflammatory cytokine levels; (2) modulation of signaling pathways such as nuclear factor kappa B (NF-κB), mitogen-activated protein kinase (MAPK), and janus kinase/signal transducer and activator of transcription (JAK/STAT); (3) amelioration of oxidative stress; and (4) regulation of immune cell homeostasis. At the pharmacokinetic level, studies show that FA is rapidly absorbed but exhibits low bioavailability, mainly due to the influence of metabolic pathways and food matrix characteristics. This review systematically summarizes the literature on the anti-inflammatory effects of FA, covering molecular mechanisms, pharmacokinetic characteristics, and application scenarios. Preclinical studies show that FA has low toxicity and good safety, demonstrating potential for development as a novel anti-inflammatory drug. However, its clinical translation is hindered by bottlenecks such as low bioavailability and insufficient human clinical data. Future research should prioritize developing novel drug delivery systems and conducting large-scale clinical trials to facilitate its clinical translation.